Increased Numbers of Circulating Tumor Cells in Thyroid Cancer Patients - Ehlers, Margret; Allelein, Stephanie; Schwarz, Franziska; Hautzel, Hubertus; Kuebart, Anne; Schmidt, Mathias; Haase, Matthias; Dringenberg, Till; Schott, Matthias (Hormone and Metabolic Research, 2018)
Circulating tumor cells (CTCs) have been shown to be a valuable prognostic marker for different solid cancers. Within the present study we quantified CTCs in thyroid cancer (TC) patients. Special focus was given to disease-free PTC patients with undetectable serum thyroglobulin (Tg) levels. Altogether, 67 TC patients (33 papillary, 20 follicular, 14 medullary) were included in the study. CTC numbers, which were normalized to 3.3×105 peripheral blood mononuclear cells, were correlated with clinical outcome. TC patients had significantly higher CTC numbers compared to controls. The number of CTCs correlated to the initial tumor stage. Importantly, in comparison to controls, differentiated TC patients with serum Tg levels<0.3 ng/ml (no evidence of tumor recurrence) revealed a significantly higher amount of CTCs, also associated to their former tumor stage. Regarding the tumor-free papillary TC (PTC) patients the number of CTCs additionally correlated to the time point of radioiodine (RI) therapy: PTC patients with RI therapies>8 years before CTC measurement had significantly higher CTC numbers compared to those with RI therapy<8 years ago. We found a clear correlation between the number of CTCs and the tumor stage. Importantly, PTC patients who are in remission may still have increased numbers of CTCs. Follow-up analyses in these patients will reveal whether these data will have a clinical impact.
Keywords: papillary thyroid cancer; follicular thyroid cancer; medullary thyroid cancer; clinical impact of CTCs